Lol I suck at math I am crying

Accepted Solution

Answer:The best thing to do would be split the fraction into two:Step-by-step explanation:(14xy^4)/(2x^3y^5) - (12x^5y^6)/(2x^3y^5)Then you would use exponent rules and subtract the exponents of the terms with the same base, so with the first term: 14/2=7 x/x^3=x^-2 y^4/y^5=y^-1 And by the same rules:12/2=6 x^5/x^3=x^2 y^6/y^5=y So we now have:7x^-2y^-1 - 6x^2y You can then also simplify it by moving the negative exponents in the first term, so the final answer would be:7/(x^2y) - 6x^2y